Glycosides in medicine: "The role of glycosidic residue in biological activity" - Kren, V; Martínková, L (Current medicinal chemistry, 2001)
Numbers of biologically active compounds are glycosides. Sometimes, the glycosidic residue is crucial for their activity, in other cases glycosylation only improves pharmacokinetic parameters. Recent developments in molecular glycobiology brought better understanding to the aglycone vs. glycoside activities, and made possible to develop new, more active or more effective glycodrugs based on these findings - very illustrative recent example is the story of vancomycin. This paper deals with an array of glycosidic compounds currently used in medicine but also with biological activity of some glycosidic metabolites of the known drugs. It involves glycosides of vitamins, polyphenolic glycosides (flavonoids), alkaloid glycosides, glycosides in the group of antibiotics, glycopeptides, cardiac glycosides, steroid and terpenoid glycosides etc. The physiological role of the glycosyl and structure-activity relations (SAR) in the glycosidic moiety (-ies) are discussed.
Keywords: Molecular Sequence Data; glykopeptidy; Vitamins; Anti-Bacterial Agents; Anthracyclines; glykosidy; Glycosides; sacharidové sekvence; Macrolides; zvířata; vitaminy; Humans; makrolidy; antibakteriální látky; antracykliny; molekulární sekvence - údaje; Carbohydrate Sequence; Glycopeptides; lidé; Animals